The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1088/1748-6041/10/1/015020
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive hydrogel-nanosilica hybrid materials: a potential injectable scaffold for bone tissue engineering

Abstract: Novel bioactive organic-inorganic hybrid materials that can serve as injectable hydrogel systems for bone tissue regeneration were obtained. The silica nanoparticles (SiNP) prepared in situ by the Stöber method were dispersed in collagen, collagen-chitosan or chitosan sols, which were then subsequently crosslinked. Laser scanning confocal microscopy studies, in which fluorescent SiNP were applied, and SEM images indicated that the nanosilica particles were distributed in the whole volume of the hydrogel matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…Other inorganic materials such as nanosilica and Bioglass have been studied for the preparation of hybrid hydrogel systems. 288,289 For example, Vishnu Priya et al 290 have developed an injectable hydrogel system by using chitin and poly(butylene succinate) loaded with fibrin nanoparticles and magnesium-doped Bioglass. This hydrogel system enhances the initiation of differentiation and expression of alkaline phosphatase and osteocalcin, thus indicating its promise for regenerating irregular bone defects.…”
Section: Injectable Hydrogels For Bone Tissue Engineeringmentioning
confidence: 99%
“…Other inorganic materials such as nanosilica and Bioglass have been studied for the preparation of hybrid hydrogel systems. 288,289 For example, Vishnu Priya et al 290 have developed an injectable hydrogel system by using chitin and poly(butylene succinate) loaded with fibrin nanoparticles and magnesium-doped Bioglass. This hydrogel system enhances the initiation of differentiation and expression of alkaline phosphatase and osteocalcin, thus indicating its promise for regenerating irregular bone defects.…”
Section: Injectable Hydrogels For Bone Tissue Engineeringmentioning
confidence: 99%
“…This is an alternative strategy to highly crosslinked hydrogels which are generally stiff materials with limited extensibility, poor swelling capability as well as slow molecular diffusion . Therefore, with the aim of designing CS hydrogels with excellent mechanical strength and high elasticity for tissue engineering and drug delivery applications, a large variety of inorganic NPs have been incorporated into hydrogels, such as silica NPs, metal NPs, hydroxyapatite (HAp) NPs, graphene oxide (GO) NPs and clay NPs . Han and Yan exploited the multifunctional groups of GO NPs to prepare supramolecular hydrogels of CS .…”
Section: Nanoparticle–hydrogel Compositesmentioning
confidence: 99%
“…The biosilica spicules are embedded into an organic matrix and it has been demonstrated that they are nontoxic for mammalian cells, already suggesting their biocompatibility . Indeed, biosilica derived from marine sponges is being considered for biomedical approaches, bone replacement and regeneration strategies in TE, specially because silica ions are known as an important element to stimulate bone formation . Bioactive silica glasses, for instance, bond and integrate to bone tissue through the formation of a silica gel layer, which attracts and stimulate osteoprogenitor cells to proliferate and to differentiate in osteoblasts, starting the synthesis and the deposition of bone organic matrix and matrix mineralization …”
Section: Sponges Composition: Interesting Elements For Bone Tissue Enmentioning
confidence: 99%
“…42 Indeed, biosilica derived from marine sponges is being considered for biomedical approaches, bone replacement and regeneration strategies in TE, 33 specially because silica ions are known as an important element to stimulate bone formation. [44][45][46] Bioactive silica glasses, for instance, bond and integrate to bone tissue through the formation of a silica gel layer, which attracts and stimulate osteoprogenitor cells to proliferate and to differentiate in osteoblasts, starting the synthesis and the deposition of bone organic matrix and matrix mineralization. 12,14 In this context, some authors have performed in vitro studies to verify the biocompatibility of biosilica derived from marine sponges.…”
Section: Biosilicamentioning
confidence: 99%